2017
DOI: 10.1158/1078-0432.ccr-17-1259
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenomic Landscape of RUNX1-mutated AML Reveals Importance of RUNX1 Allele Dosage in Genetics and Glucocorticoid Sensitivity

Abstract: -mutated () acute myeloid leukemia (AML) is associated with adverse outcome, highlighting the urgent need for a better genetic characterization of this AML subgroup and for the design of efficient therapeutic strategies for this disease. Toward this goal, we further dissected the mutational spectrum and gene expression profile of AML and correlated these results to drug sensitivity to identify novel compounds targeting this AML subgroup. RNA-sequencing of 47 primary AML specimens was performed and sequencing r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 49 publications
4
34
0
Order By: Relevance
“…The enrichment of RUNX1 mutations in pDC-AML implies a crucial role of this genetic event and downstream altered gene regulatory networks in pDC differentiation. Prior studies have shown that pDCrelated transcription factors are highly expressed in RUNX1 mutated AML (64)(65)(66), which is further supported by our data. Our study also provides direct evidence that the leukemic blasts from RUNX1 mutated AML are primed to differentiate into pDCs.…”
Section: Discussionsupporting
confidence: 91%
“…The enrichment of RUNX1 mutations in pDC-AML implies a crucial role of this genetic event and downstream altered gene regulatory networks in pDC differentiation. Prior studies have shown that pDCrelated transcription factors are highly expressed in RUNX1 mutated AML (64)(65)(66), which is further supported by our data. Our study also provides direct evidence that the leukemic blasts from RUNX1 mutated AML are primed to differentiate into pDCs.…”
Section: Discussionsupporting
confidence: 91%
“…A recent pre-clinical study demonstrated that AML cells with RUNX1 mutations were sensitive to glucocorticoids while earlier in vitro studies suggested an antileukemic activity in AML with the t(8;21)/ RUNX1-RUNX1T1 translocation. 21 , 22 To find out whether other molecular subgroups could benefit from glucocorticoids, we first tested the in vitro activity of dexamethasone against AML cell lines with various genetic backgrounds. As expected, dexamethasone had no significant activity as a single agent in most AML cell lines cultured in suspension ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Chemogenomic landscape of RUNX1-mutated AML reveals importance of RUNX1 allele dosage in genetics and glucocorticoid sensitivity. Results show the profound impact of RUNX1 allele dosage on gene expression profile and glucocorticoid sensitivity in AML, which may lead to drug repurposing and improved disease characterization [79].…”
Section: Runx1mentioning
confidence: 99%